The Effect of Aluminum Deformation Conditions on Microhardness and Indentation Size Effect Characteristics - Peter Blaško; Jozef Petrík; Marek Šolc; Mária Mihaliková; Lenka Girmanová; Alena Pribulová; Peter Futáš; Joanna Furman; Kuczyńska-Chałada Marzena (Crystals)
The degree and speed of deformation are factors that influence microstructure and mechanical properties. Aluminum (99.5%) was used as the test material in this experiment. This material is currently mainly used in the electrical industry to manufacture conductors as a substitute for the more expensive copper. The cylindrical samples were deformed at a strain rate of up to 2500 s−1, and the degree of deformation was up to 85%. At the point place of maximum deformation, usually in the center of the sample, the microhardness was measured under various loads, between 10 gf and 100 gf. The obtained data were used to determine the characteristics or parameters of the indentation size effect (ISE) and the influence of the deformation conditions on the microhardness. The results obtained were processed by linear regression analysis, followed by the creation of deformation maps.